Regional cerebral oxygen saturation during cardiopulmonary resuscitation as a predictor of return of spontaneous circulation and favourable neurological outcome – A review of the current literature. (April 2018) - Schnaubelt, S.; Sulzgruber, P.; Menger, J.; Skhirtladze-Dworschak, K.; Sterz, F.; Dworschak, M.
Abstract: Introduction: Regional cerebral oxygen saturation (rSO2) can be measured non-invasively even at no- or low-flow states. It thus allows assessment of brain oxygenation during CPR. Certain rSO2 values had been associated with return of spontaneous circulation (ROSC) and neurological outcome in the past. Clear-cut thresholds for the prediction of beneficial outcome, however, are still lacking. Methods: We conducted a database search to extract all available investigations on rSO2 measurement during CPR. Mean, median, and ΔrSO2 values were either taken from the studies or calculated. Thresholds for the outcome "ROSC" and "neurological outcome" were sought. Results: We retrieved 26 publications for the final review. The averaged mean rSO2 for patients achieving ROSC was 41 ± 12% vs. 30 ± 12% for non-ROSC (p = .009). ROSC was not observed when mean rSO2 remained <26%. In ROSC patients, ΔrSO2 was 22 ± 16% vs. 7 ± 10% in non-ROSC patients (p = .009). A rSO2 threshold of 36% predicted ROSC with a sensitivity of 67% and specificity of 69% while ΔrSO2 of 7% showed a sensitivity of 100% and a specificity of 86% (AUC = 0.733 and 0.893, respectively). Mean rSO2 of 47 ± 11% was associated with favourable and 38 ± 12% with poor neurological outcome. There was, however, a great overlap between groups due to scarce data. Conclusion: Higher rSO2 consistently correlated with increased rates of ROSC. The discriminatory power of rSO2 to prognosticate favourable neurological outcome remains unclear. Measuring rSO2 during CPR could potentially facilitate clinical decision-making.